Tendências futuras de evolução das qualificações na Europa - Paulos, Margarida Ramires (2008)
The aim of this report is to highlight the importance of foresight exercises as a necessary tool to help the decision makers, allowing through projections and identification of the main trends, the identification of the key variables of the process and which ones may have more influence in the process of evolution of societies. It will be presented some examples of prospective methods and also scenarios construction. One example is the European project WORKS (Work organization restructuring in the knowledge society) that pretend to built a set of scenarios about the possible evolution of work in Europe in a short, medium and long term, stressing the key variables that may have an important role in the process and their interconnections. Another exemple is the report ‘Future skill needs in Europe’ prepared in 2008 by Cedefop, that presents data about the future development of employment by industry, occupation and qualification by 2015.